1994
DOI: 10.1128/jvi.68.5.2937-2946.1994
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus maturational proteinase: expression in Escherichia coli, purification, and enzymatic characterization by using peptide substrate mimics of natural cleavage sites

Abstract: The proteolytic processing of the human cytomegalovirus (HCMV) assembly protein, resulting in truncation of its C terminus, is an essential step in virion maturation. The proteinase responsible for this cleavage is the amino-terminal half of the protein encoded by the UL8Oa open reading frame. We have obtained high expression levels of this 256-amino-acid HCMV proteinase, assemblin, in Escherichia coli. In addition to the 28-kDa proteinase, a 15-kDa protein comprising the first 143 amino acids and a 13-kDa pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Recently, Burke et al [11] demonstrated that glycerol increased the rate of substrate cleavage by approximately ninefold for the HCMV protease and, under these conditions, we observed a similar increase. However, the addition of glycerol did not significantly alter the relative hydrolysis rates of the various peptides.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Recently, Burke et al [11] demonstrated that glycerol increased the rate of substrate cleavage by approximately ninefold for the HCMV protease and, under these conditions, we observed a similar increase. However, the addition of glycerol did not significantly alter the relative hydrolysis rates of the various peptides.…”
Section: Resultssupporting
confidence: 86%
“…Studies have demonstrated that the catalytic domain of the protease is contained in the first 256 amino acids of the protease [5,8,10,111, and is released by the release cleavage. A third autoprocessing site has been identified in the catalytic domain of HCMV protease, at Ala143-Ala144 and is proposed to inactivate the enzyme [8,11,121. HSV-1 also encodes a protease, which cleaves itself and the HSV-1 assembly protein, ICP35 .…”
mentioning
confidence: 99%
“…It has been suggested that the hCMV protease is a serine protease based on its chemical reactivity toward classical serine protease inhibitors (6), and recent site-directed mutagenesis data (7) have implicated the catalytic triad of hCMV protease to be Ser-132, His-63, and Glu-122. However, the catalytic efficiency of the hCMV protease is orders of magnitude less than that expected of a classical serine protease, and no amino acid sequence homology has been found between this enzyme and the well characterized serine proteases (7,8).…”
mentioning
confidence: 95%
“…In addition, the different fluorophore moieties could contribute to altered subsite binding properties; indeed, trypsin and trypsin D102N appear to discriminate between the two substrates as well. The absence of the aspartic acid in the active site of the viral Pr, while reducing the enzyme's velocity, also results in less sensitivity to standard serine protease inhibitors such as phenylmethylsulfonyl fluoride and tosyl lysyl chloromethyl ketone (8,14,39,62,66). This was similarly observed for trypsin D102N (15).…”
Section: Discussionmentioning
confidence: 86%